Central Asian Republic’s Approaches to the Development of the Regional Hydroeconomic Sector - B. N. Mubarakshin (Vestnik MGIMO-Universiteta)
Mechanisms of centralized planning during the soviet period enabled to maintain balance of interests among hydrocarbon-rich Kazakhstan, Uzbekistan Turkmenistan on one hand and having enormous reserves of water Tajikistan and Kyrgyzstan on the other. After the collapse of the united state the latter group found out themselves under disadvantage: they have to buy oil and natural gas at world prices. At the same time downstream countries have continued to use their water resources at no cost. This standing cannot go on forever. Since the middle of the 1990s expert circles of Kyrgyzstan and Tajikistan have been urging to recognize water resources as full-fledged goods. The idea is also met support in governmental circles. At the turn of the century Kyrgyz authorities even adopted notorious laws to regulate the introduction of paid water consumption at interstate level. Today expert circles of various Central Asian republics take polar views on the development of regional hydroeconomic sector. Midstream and downstream countries of Amu Darya and Syr Darya (Uzbekistan, Kazakhstan and Turkmenistan) insist on retaining of the status quo in regional water distribution. At the same time the upstream countries persist in revision of old soviet system of water distribution. In addition, in spite of categorical protest of Uzbekistan, they are going to construct a number of large hydrotechnic buildings in the rivers. Among this antagonisms they often forget or just disregard the fact that the hydroeconomic sector is a comprehensive whole and therefore should develop within one integrated process on the basis of interstate cooperation of the regional republics.